Fear Not the Trunchbull: How Teaching from a Humorous Outlook Supports Transformative Learning - Kathleen J Cassity (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
Empirical and historical evidence suggest that humor is a key tool for discovering ways in which learning can become transformative.